Effects of extrusion on ileal and total tract nutrient and energy digestibility of untoasted soybean meal in weanling pigs - Milani, Natália Cristina; Paula, Vinicius Ricardo Cambito de; Azevedo, Cândida Pollyanna Francisco; Sedano, Anderson Aparecido; Scarpim, Lucas Bassi [UNESP]; Moreira Junior, Hélio; Duarte, Dave Hanneman Alves; Carciofi, Aulus Cavalieri [UNESP]; Trindade Neto, Messias Alves da; Ruiz, Urbano dos Santos (Elsevier, 2022)
This study evaluated the nutrient and energy digestibility of untoasted soybean meal (USM) extruded at three different temperatures, compared to toasted soybean meal (SBM), in weaned piglets. Forty crossbred barrows (25-D-old and 7.69 ± 0.89 kg BW) were allotted to a N-free diet or to four test diets in a randomized complete block design with 8 replications per treatment. The N-free diet was used to determine endogenous losses of amino acids (AA), and test diets contained 30% of each test ingredient as the only source of protein and AA: untoasted soybean meal extruded at 86 °C (USM86), 120 °C (USM120) or 149 °C (USM149) or with SBM, as a control diet. Titanium dioxide was added to the diets as an indigestible marker. After a 5 d adaptation period, feces were collected over a 5 d period and samples of ileal digesta were collected after piglets euthanasia. The apparent total tract digestibility (ATTD) of dry matter (DM), gross energy (GE), ether extract (EE), crude protein (CP), neutral detergent fiber (aNDF) and acid detergent fiber (ADF), and apparent (AID) and standardized (SID) ileal digestibility of AA, and their respective digestible values were evaluated. Analysis of variance was performed and the means were compared by Tukey when P < 0.05. Increasing extrusion temperature decreased concentrations of soybean trypsin inhibitors. Untoasted soybean meal extruded at 86 °C showed lower (P < 0.05) ATTD of DM (7–11%), GE (3–4%), and CP (10–13%) compared to SBM, USM120 and USM149, which did not differ. The ATTD of EE of SBM was 17–19% higher (P < 0.05) than that of USM86 and USM120, which were similar to each other and greater (P < 0.05) than that of USM149. Extrusion of USM at 86 oC was insufficient to inactivate anti-nutritional factors and reduced (P < 0.05) AID and SID of CP and AA by 25–29% and 27–31%, respectively, compared to SBM, USM120 and USM149, which were mostly similar. Soybean meal extruded at 120 and 149 °C presented a similar nutritional value to toasted soybean meal.
Keywords: Anti-nutritional factor; Apparent and standardized ileal digestibility; Feed processing; Trypsin inhibitor